2010
DOI: 10.1002/ctpp.201010156
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless Drift Waves Ranging from Current‐Driven, Shear‐Modified, and Electron‐Temperature‐Gradient Modes

Abstract: The specific history of collisionless drift waves is marked by focusing upon current-driven, shear-modified, and electron-temperature-gradient modes. Studies of current-driven collisionless drift waves started in 1977 using the Innsbruck Q machine and was continued over 30 years until 2009 with topics such as plasma heating by drift waves in fusion-oriented confinement and space/astrophysical plasmas. Superposition of perpendicular flow velocity shear on parallel shear intensively modifies the drift wave chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The k 2 multiplier in the integrand ensures that the contribution from the large non-universal scales is suppressed. For k > 1/η we find the dissipation subrange, which in the classical Heisenberg analysis (Heisenberg, 1948;Chandrasekhar, 1949) is found to decrease like k −7 . This particular results seems to agree well with some observations but is nonetheless suspect since it predicts that higher-order velocity derivatives (∇ j u) 2 = ∞ 0 k 2j S(k)dk should be divergent for some large j .…”
Section: Models For Strong Turbulence In Fluids and Plasmasmentioning
confidence: 62%
See 1 more Smart Citation
“…The k 2 multiplier in the integrand ensures that the contribution from the large non-universal scales is suppressed. For k > 1/η we find the dissipation subrange, which in the classical Heisenberg analysis (Heisenberg, 1948;Chandrasekhar, 1949) is found to decrease like k −7 . This particular results seems to agree well with some observations but is nonetheless suspect since it predicts that higher-order velocity derivatives (∇ j u) 2 = ∞ 0 k 2j S(k)dk should be divergent for some large j .…”
Section: Models For Strong Turbulence In Fluids and Plasmasmentioning
confidence: 62%
“…Enhanced growth rates of drift wave instabilities can be found with field-aligned currents (Hatakeyama et al, 1980(Hatakeyama et al, , 2011Garcia and Pécseli, 2013): in these cases the restriction on mean free paths is of minor consequence.…”
Section: Resistive Drift Waves With Ion-electron Collisionsmentioning
confidence: 99%
“…In this kinetic model, is replacing the assumption of Boltzmann‐distributed electrons. In, for instance, laboratory experiments, it has been demonstrated that drift waves can be made unstable by currents along the magnetic field lines [ Hatakeyama et al , ]. To estimate the growth rate under the present conditions, we again assume quasi‐neutrality n e ≈ n i = n and combine and to get ωωCs2()k2normalΩci2kz2ω2+ikzgω2=1+ωUkzωkzuTeZ()ωUkzkzuTe0.3em.…”
Section: Drift Wave Instabilitymentioning
confidence: 99%
“…First, a novel method to control plasma structures, such as electron temperature gradient (ETG) [1] in magnetized non-equilibrium plasmas, has been developed for understanding and controlling anomalous plasma heat transport to improve plasma confinement [2]. Normally, because the perpendicular spatial scale of electron heat transport is much smaller than that for ion heat transport, heat transport models are based on ion scale fluctuations, such as the ion temperature gradient (ITG) mode and the drift wave (DW) mode [3,4]. Recently, on the other hand, the anomalous electron heat transport is also a big issue [5], which is considered to be caused by the ETG driven instability [6,7].…”
Section: Introductionmentioning
confidence: 99%